Qualidade do leite em sistemas de base agroecológica e em sistemas convencional - Tinini, Rodrigo Cesar dos Reis (2015)
The demand for safer food comes highlighting the need to assess the quality of food production, and milk is a good example as the most complete food. Thus, this study aimed to evaluate the quality and milk composition, fat, protein, lactose, total solids, somatic cell count (SCC) and total bacterial count (TBC) in agroecological production systems and conventional systems, relating with the frequency of milking practices types of installations, climatic factors, frequency and type of food provided. Data collection was performed in the years 2013 and 2014, by applying a semi-structured questionnaire guide, to identify management strategies adopted by producers in the dairy production systems (DPS), in the municipality of Diamante d'Oeste-PR, and DPS in the city of Toledo-PR, both in the western region of Paraná, held monthly collections of milk for composition analysis and quality. For the statistical analysis a cluster analysis was done to form groups and then went round one descriptive statistics on the practices carried out by groups, being also applied a t Test for independent samples at significance level of 5%, as well as a correlation test. The cluster classification analysis allowed grouping the initial group of 40 production systems in 3 homogeneous groups of systems: Group 1, group with better quality compared to normative instruction 62 (IN62), with SCC values of 290.97 (cel x1000/mL) and TBC 226.40 (x1000 CFU/mL); Group 2, with SCC 645.55 (x1000 cel/mL) and TBC 823.43 (x1000 CFU/mL), out of IN 62; and Group 3, with CCS 400.00 (x1000 cel/mL), low and high value of TBC 2116.87 (x1000 CFU/mL), out of IN 62. There were significant differences for protein, lactose, total solids and TBC (total bacterial count), there was correlation between the components of the analyzed milk, and no influence of rainfall during the year on the composition and quality of milk. The milk composition changed when comparing the DPS's agro-ecological and conventional base during the year. The milk composition was influenced by climatic factors and the animal feed, varied between the months of the year, and the quality is mainly compromised by practices hygiene and managements adopted